Anomalous signal from S atoms in protein crystallographic data from an X‐ray free‐electron laser. (1st May 2013) - Barends, Thomas R. M.; Foucar, Lutz; Shoeman, Robert L.; Bari, Sadia; Epp, Sascha W.; Hartmann, Robert; Hauser, Gunter; Huth, Martin; Kieser, Christian; Lomb, Lukas; Motomura, Koji; Nagaya, Kiyonobu; et al.
<x xml:space="preserve">Abstract</x> X‐ray free‐electron lasers (FELs) enable crystallographic data collection using extremely bright femtosecond pulses from microscopic crystals beyond the limitations of conventional radiation damage. This diffraction‐before‐destruction approach requires a new crystal for each FEL shot and, since the crystals cannot be rotated during the X‐ray pulse, data collection requires averaging over many different crystals and a Monte Carlo integration of the diffraction intensities, making the accurate determination of structure factors challenging. To investigate whether sufficient accuracy can be attained for the measurement of anomalous signal, a large data set was collected from lysozyme microcrystals at the newly established `multi‐purpose spectroscopy/imaging instrument' of the SPring‐8 Ångstrom Compact Free‐Electron Laser (SACLA) at RIKEN Harima. Anomalous difference density maps calculated from these data demonstrate that serial femtosecond crystallography using a free‐electron laser is sufficiently accurate to measure even the very weak anomalous signal of naturally occurring S atoms in a protein at a photon energy of 7.3 keV.